Edukacja jako politicum – debata wokół integracyjnej roli holenderskiego „państwa edukacyjnego” - Hildebrandt-Wypych, Dobrochna (Wydawnictwo Naukowe UAM, 2014)
The aim of the article is to reflect upon the historically unprecedented approach of the Netherlands to the challenge of defining its role as an “investor” in human capital in the era of industrialization, a “modernizer” of social relations in the period of democratization, as well as a “creator” of the nationwide integration policy in an era of increasing cultural diversity. There are two indisputable aspects of the so-called “educational state” in contemporary Dutch education policy (A. Weymann): the key role of education as an instrument of political legitimacy through meritocracy and the importance of education as a “stimulator” of economic growth through investment in human capital. However, there is growing controversy over the way in which the “educational state” should define its role as a public space for social integration through culture and ideology.
Education as a Politicum: the Debate Around the Integrative Role of the Dutch “Educational State"
Keywords: education policy; education in the Netherlands; politics of accommodation; integration; multicultural society